Mathematics learning community: a case study / Teoh Sian Hoon ... [et al.] - Hoon, Teoh Sian; Mohd Yusof, Mohammad Mubarrak; Mohd Rasid, Nor Syazwani; Mohamed, Siti Rosiah; Mohd, Ainun Hafizah (Universiti Teknologi MARA, 2021)
The desire to equip students with 21st-century skills has prompted teachers to find alternative ways to promote real learning of mathematics. One of these ways includes building communities of best practices, with the collaborative efforts of parents. This study aims to investigate how mathematics teaching communities develop mathematical knowledge and skills in students. This study interviewed four teachers for insights into their teaching practices, specifically, how they built a learning community to foster the learning of mathematics. The findings showed that the teachers, working with parents, provided substantial support to develop students' knowledge of mathematics and 21st-century skills, such as life skills. This study shows how mathematical knowledge and skills can be developed within a community with little access to advanced technology and how students can be supported to acquire life-long learning skills.